(untitled) (ModaPalavra e-periódico, 2022)
The text presents a methodological experience lived in a Fashion Design course in the city of Rio de Janeiro, Brazil, made with students from the last semester during the development of their conclusion projects. It presents the study of a tool for the creative process and some results obtained. The text also reflects on the importance of textile material as a creative element and not just as a means for clothing